Complexity Science: New Emerging Approach for Health Professionals - N Keshavarz; I Huges; F Khavarpour (Tehran University of Medical Sciences, 2005)
Complexity science is about complex adaptive systems (CAS) and provides important concepts and tools for responding to challenge of health care in 21st century and as Holland describes, it is the science of 21st century. In this presentation, I will discuss some of the potential advantages of applying complexity science in my research in school health promotion. Complexity science originates from systems thinking and has been applied in biology, behaviour science, management, business, computer science and mathematics, physics and more recently, in health care. There are few reports about application of this theory in health but they look promising or at least challenging. A CAS is a collection of autonomous, interactive, and adaptive agents that act freely in diverse ways, which are unpredictable and, non-linear but interconnected. It is an ever-changing system, typically with fuzzy boundaries, built of multi-layer nested systems. The evolution of one system influences and influenced by that of other systems. Organisms such as human beings and organizations like health care organizations are good examples of these systems having Variation and non-linear pattern of cause and effect, interactions and change as concepts of CAS. One of the key benefits of the complex adaptive system approach is that it helps you see yourself in the context of a population of agents and helps you see your actions in the context of a population of strategies. In designing my research, I am able to choose from among a range of strategies, otherwise called research methods. I selected semi-structured interviews, participant observation and document analysis. I am interviewing, I meet and interact with teachers who are autonomous agents who make choices what strategies in a context of departmental and school policies described in documents.